The Effect of Using Various Doses of Organic Cow Manure Fertilizer on the Growth and Production of Green Bean Plants - Hujemiati; Djabar, Murni; Darma; Hasmidar (International Journal of Integrative Sciences, 2024)
This research is in the form of an experiment that aims to determine the effect of using various organic fertilizers of cow dung on the growth and production of green bean plants carried out in Kanco Village, Cina District, Bone Regency and its implementation began in March to May 2023. This experiment was arranged based on a Randomized Block Design (RAK) consisting of 4 treatments, each repeated 3 times, in 1 plot there were 96 plants. Sampling was taken from 30% of the middle plants, so there were 5 plants. In this experiment there were 12 plots, so that 60 plants would be studied. The results of the experiment showed that the effect of using various doses of organic fertilizers of cow dung on fertilizer treatment with a dose of 5 tons/Ha or 3000 grams/plot showed the highest results of all parameters observed and for the production of sample plants was 15.54 grams and production per plot 1.49 kg